PENERAPAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA MATERI HAK DAN KEWAJIBAN DI KELAS V UPT SDN 060827 MEDAN AMPLAS - Norasi Wita Simanjuntak; Arrini Shabrina Anshor; Nur Asyah; Irwan Veri; Prontina Situmorang (STKIP Subang, 2024)
This study aims to improve student learning outcomes by using the Cooperative Integrated Reading and Composition learning model in the Pancasila Education subject on the material of rights and obligations. The subjects in this study were 30 fifth grade students. The techniques used by researchers in collecting data were observation and tests. The learning model used in this study is the Cooperative Integrated Reading and Composition learning model. This study shows an increase in student learning outcomes in the material of rights and obligations of Learning 1 and 2 in class V of SD Negeri 060827 Medan Amplas in the 2024/2025 Academic Year. This is evident from the results of the study conducted during the pretest (initial test) which received a complete score of 9 students or 30% while those who received an incomplete score were 21 students or 70, with an average learning outcome of 52. The results of the study in cycle I increased to 13 students who completed or 43% while those who did not complete were 17 students or 57% with an average score of 64.96. In cycle II, the completion of student learning outcomes increased to 26 students or 87% of students who completed while 4 people or 13% did not complete with average values ​​of 80.47, so there was an increase in cycle I to cycle II and had met the predetermined completion. Furthermore, from the results of observations of teacher activities in implementing learning in cycle I, an average value of 72% (Good) was obtained and in cycle II it increased to 92% (Very Good) and the results of observations of student activities in cycle I obtained an average value of 62% (Good) and increased in cycle II to 92% (Very Good).